Silencing of the TRIM58 Gene by Aberrant Promoter Methylation is Associated with a Poor Patient Outcome and Promotes Cell Proliferation and Migration in Clear Cell Renal Cell Carcinoma - Gan, Ying; Cao, Congcong; Li, Aolin; Song, Haifeng; Kuang, Guanyu; Ma, Binglei; Zhang, Quan; Zhang, Qian (Frontiers in Molecular Biosciences, 2021)
To investigate the underlying molecular mechanism of tripartite motif-containing 58 (TRIM58) in the development of clear cell renal cell carcinoma (ccRCC), we explored TRIM58 expression and methylation in tumor tissues and the association with clinicopathological features and prognosis of tissue samples; Moreover, we examined the direct gene transcription of TRIM58-specific DNA demethyltransferase (TRIM58-TET1) by the CRISPR-dCas9 fused with the catalytic domain of TET1 and the biological functions in RCC cells. In this study, we demonstrate that TRIM58 is frequently downregulated by promoter methylation in ccRCC tissues, associated significantly with tumor nuclear grade and poor patient survival. TRIM58-TET1 directly induces demethylation of TRIM58 CpG islands, and activates TRIM58 transcription in RCC cell lines. Besides, DNA demethylation of TRIM58 by TRIM58-TET1 significantly inhibits cell proliferation and migration Overall, our results demonstrate that TRIM58 is inactivated by promoter methylation, associates with tumor nuclear grade and poor survival, and TRIM58 DNA demethylation could directly activate TRIM58 transcription and inhibit cell proliferation and migration in RCC cell lines.